Enriching plant diversity in grasslands by large-scale experimental sward disturbance and seed addition along gradients of land-use intensity. (16th June 2016) - Klaus, Valentin H.; Schäfer, Deborah; Kleinebecker, Till; Fischer, Markus; Prati, Daniel; Hölzel, Norbert
Abstract: Aims: The relationship between biodiversity and ecosystem functioning is among the most active areas of ecological research. Furthermore, enhancing the diversity of degraded ecosystems is a major goal in applied restoration ecology. In grasslands, many species may be locally absent due to dispersal or microsite limitation and may therefore profit from mechanical disturbance of the resident vegetation. We established a seed addition and disturbance experiment across several grassland sites of different land use to test whether plant diversity can be increased in these grasslands. Additionally, the experiment will allow us testing the consequences of increased plant diversity for ecosystem processes and for the diversity of other taxa in real-world ecosystems. Here, we present details of the experimental design and report results from the first vegetation survey 1 year after disturbance and seed addition. Moreover, we tested whether the effects of seed addition and disturbance varied among grassland depending on their land use or pre-disturbance plant diversity. Methods: A full-factorial experiment was installed in 73 grasslands in three regions across Germany. Grasslands were under regular agricultural use, but varied in the type and the intensity of management, thereby representing the range of management typical for large parts of Central Europe. The disturbance treatment consisted of disturbing the top 10cm of the sward using a rotavator or rotary harrow. Seed addition consisted of sowing a high-diversity seed mixture of regional plant species. These species were all regionally present, but often locally absent, depending on the resident vegetation composition and richness of each grassland. Important Findings: Seven months after sward disturbance, respective plots had significantly increased in bare soil, seedling species richness and number of seedlings. Seed addition had increased plant species richness, but only in combination with sward disturbance. The increase in species richness, when both seed addition and disturbance was applied, was higher at high land-use intensity and low resident diversity. Thus, we show that at least the early recruitment of many species is possible also at high land-use intensity, indicating the potential to restore and enhance biodiversity of species-poor agricultural grasslands. Our newly established experiment provides a unique platform for broad-scale research on the land-use dependence of future trajectories of vegetation diversity and composition and their effects on ecosystem functioning.